Determination of Butyrate Synthesis Capacity in Gut Microbiota: Quantification of but Gene Abundance by qPCR in Fecal Samples - Daskova, Nikola; Heczkova, Marie; Modos, Istvan; Videnska, Petra; Splichalova, Petra; Pelantova, Helena; Kuzma, Marek; Gojda, Jan; Cahova, Monika (Biomolecules, 2021)
Butyrate is formed in the gut during bacterial fermentation of dietary fiber and is attributed numerous beneficial effects on the host metabolism. We aimed to develop a method for the assessment of functional capacity of gut microbiota butyrate synthesis based on the qPCR quantification of bacterial gene coding butyryl-CoA:acetate CoA-transferase, the key enzyme of butyrate synthesis. In silico, we identified bacteria possessing but gene among human gut microbiota by searching but coding sequences in available databases. We designed and validated six sets of degenerate primers covering all selected bacteria, based on their phylogenetic nearness and sequence similarity, and developed a method for gene abundance normalization in human fecal DNA. We determined but gene abundance in fecal DNA of subjects with opposing dietary patterns and metabolic phenotypes-lean vegans (VG) and healthy obese omnivores (OB) with known fecal microbiota and metabolome composition. We found higher but gene copy number in VG compared with OB, in line with higher fecal butyrate content in VG group. We further found a positive correlation between the relative abundance of target bacterial genera identified by next-generation sequencing and groups of but gene-containing bacteria determined by specific primers. In conclusion, this approach represents a simple and feasible tool for estimation of microbial functional capacity.
Keywords: Feces; polymerázová řetězová reakce; fylogeneze; Obesity; Gene Dosage; lidé; lidé středního věku; feces; mladiství; obezita; fenotyp; reprodukovatelnost výsledků; Statistics, Nonparametric; Butyrates; Adolescent; Gastrointestinal Microbiome; Young Adult; Polymerase Chain Reaction; Phenotype; Vegans; vegani; Adult; DNA bakterií; střevní mikroflóra; Middle Aged; Genes, Bacterial; Phylogeny; Reproducibility of Results; butyráty; Humans; neparametrická statistika; dospělí; DNA, Bacterial; mladý dospělý; bakteriální geny; genová dávka